An annotated che - Allen, Gerald R (1997)
Clipperton Atoll is the most isolated, most westerly and largest coral reef in the tropical eastero Pacific (TEP). We collected and recorded fishes to depths of 60m during a two week visit in April 1994. Previous collections were made late last century andby expeditions from Scripps Institution of Oceanography in 1956 and 1958. One hundred and fifteen identified species from 89 genera and 43 farnilies are now known from the island. The most speciose families present at the island are moray eels (Muraenidae, 14 species), jacks (Carangidae, 11 species), wrasses (Labridae, 8 species), surgeonfishes (Acanthuridae, 8. species), squirrelfishes (Holocentridae, 5 species), groupers (Serranidae, 5 species), and triggerfishes (Balistidae, 5 species). These represent -14% of the TEP nearshore fish fauna and 40% of its genera. The 115 species inelude 14 offshore pelagic species, 22 inshore pelagic and midwater species, 70 demersal species that live 011 hard reef substrata, and nine demersal species tltat live in or feed on unconsolídated substrata (rubble and sand). Among the IOlnon-oceanie species, 68% ate carnivoreson mobile organisms, 9.2% feed on sessile benthie invertebrates, 12.9% are planktivorous, and 17.8% are benthie feeding herbivores. At least 70 of the non-oceanie speeies appear to have resident (i.e. self sustaining) populatións at the atoll, while 17 species probably are vagrants. Clipperton's fishes inelude 63 rranspacific species (i.e. species that also oceur on the westero side of the Bastero Pacifie Barrier) and 52 species endemie to the TEP. While most (36) of the TEP species oeeur throughout the region, four oceur o¡:¡ly at boh Clipperton and the Revillagigedos, the nearest shoal habitat, 950 km to the north. Nine species or subspeeies Crom seven families a re endemie to Clipperton. They represent 11.3% of Clipperton's demersal shorefishes. The sister speeies of one of them likely is a transpacifie species, while the sister species of the other eight Iikely are TEP speeies.